2022
DOI: 10.1177/11795514221074672
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthyroidism and Liver Dysfunction: A Review of a Common Comorbidity

Abstract: Deranged liver enzymes due to hyperthyroidism rather than intrinsic liver pathology are not uncommon. The reported prevalence of liver biochemical abnormalities in patients with untreated thyrotoxicosis varies widely ranging from 15% to 76%. The suggested causes of liver dysfunction include direct hepatocyte injury, co-morbid heart failure, associated autoimmune conditions (especially in the setting of Graves’ Disease), preexisting liver disease and drugs including antithyroid medications. Although, some patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 29 publications
(51 reference statements)
0
23
0
10
Order By: Relevance
“…1 Impact of thyroid function on male and female reproductive system even symptomatic hypocortisolemia may be present [25]. In addition, prolonged hyperthyroidism leads to direct liver toxicity and hepatocyte anoxia with impaired liver function [26]. In patients with GD, LH secretion is increased compared to euthyroid patients [27].…”
Section: Impact On Spontaneous Conception Thyrotoxicosis Resultsmentioning
confidence: 99%
“…1 Impact of thyroid function on male and female reproductive system even symptomatic hypocortisolemia may be present [25]. In addition, prolonged hyperthyroidism leads to direct liver toxicity and hepatocyte anoxia with impaired liver function [26]. In patients with GD, LH secretion is increased compared to euthyroid patients [27].…”
Section: Impact On Spontaneous Conception Thyrotoxicosis Resultsmentioning
confidence: 99%
“…(1) direct liver toxicity from exposure of excess thyroid hormones; (2) liver cell degeneration from accelerated decomposition of liver glycogen and protein; (3) congestive hepatopathy from thyrotoxic heart failure; (4) previous underlying liver disease; (5) toxicity and injury by antithyroid medications; (6) autoimmune-related liver injury. 5,6 Retrospective studies also reported that the risk factors of liver dysfunction were age, course of Graves' disesase, heart rate, weight of the thyroid gland, FT4 level, TR-antibodies, and TPO-antibodies. 7 Congestive hepatopathy is described as manifestations of chronic, passive congestion of the liver in the setting of heart failure or other cardiac defects that result in elevation of central venous pressure.…”
Section: Discussionmentioning
confidence: 99%
“…7 Congestive hepatopathy is described as manifestations of chronic, passive congestion of the liver in the setting of heart failure or other cardiac defects that result in elevation of central venous pressure. 6,8 Circulatory system disorders may cause hepatic dysfunction due to several mechanisms. First, right ventricular dysfunction increases preload or central venous pressure that can cause direct liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…The role of hyperthyroidism and liver dysfunction has been reported[ 23 ]. Hepatic biochemical abnormalities in untreated thyrotoxicosis patients is closed between [15%-76%], which may be explained by the conditions such as: direct liver cell injury, heart failure comorbidity, underlying autoimmune disorders a fortiori in hyperthyroidism, preexisting hepatic disease, and drugs combining antithyroid medicine.…”
Section: Liver Managementmentioning
confidence: 99%
“…A timely initiation of thionamides allows to normalize hepatic enzymes levels. Clinicians should suspect hyperthyroidism in patients with unexplained hepatic defect or unexplained Jaundice[ 23 ].…”
Section: Liver Managementmentioning
confidence: 99%